Project Based Blended Learning To Improve Students Creativity In Sepak Takraw - Yahya Eko Nopiyanto; Septian Raibowo; Yarmani Yarmani; Andika Prabowo (UNIB Press, 2021)
Creativity is a demand in 21st-century learning but is often ignored by lectures in the learning process of Sepak Takraw. So that we need a way to improve creativity in students through appropriate learning models. The purpose of this research is to improve the creativity of physical education students in developing Sepak Takraw learning materials. The research method used was classroom action with two cycles. The subjects in this study were students in the seventh-semester physical education, totaling 33 students. Data collection techniques and instruments used observation sheets to assess the product of the resulting project, namely the Sepak Takraw learning video. The results showed that in cycle 1 the classical completeness of the students was 70%, and in cycle 2 the classical completeness of the students was 90%. The conclusion in this study is that the application of project-based blended learning can increase creativity for students making Sepak Takraw learning videos.